Irish data on the safety and efficacy of vedolizumab in the treatment of inflammatory bowel disease. (2nd July 2020) - Judge, Ciaran; McGettigan, Neasa; Ryan, Timothy; Hazel, Karl; Singh, Pamla; Parihar, Vikrant; Stack, Roisin; O'Connor, Anthony; Dunne, Cara; Cullen, Garret; Egan, Laurence; Harewood, Gavin; et al.
Abstract: Introduction: Vedolizumab (VDZ) is a monoclonal antibody designed to inhibit α4β7 integrin and result in gut-selective anti-inflammatory activity. Real-world data are important in providing information to clinicians on the effectiveness and safety of this agent. Methods: A retrospective, multi-centre study was conducted across 9 Irish academic centres. Adult (≥18 years) patients receiving VDZ for active IBD (ulcerative colitis [UC] or Crohn's disease [CD]) with at least 6 months follow-up were included in the study cohort. Primary study endpoints were defined as 3-month clinical response and 6-month corticosteroid-free remission. Secondary endpoints included 3-month corticosteroid-free clinical remission, 6-month clinical response, change from baseline in CRP, albumin and faecal calprotectin, and adverse events. Results: One hundred and twenty-nine patients were included in total (64 UC, 65 CD). In the UC cohort, baseline median PMCS was 7 [0 – 9] and 78.1% had prior anti-tumour necrosis factor alpha (anti-TNFα) exposure. Three-month and 6-month endpoints were achieved in 40% and 31%, respectively. Milder disease, CRP, albumin and prior anti-TNFa were associated with endpoints. One minor adverse event was documented. In the CD cohort, baseline HBI was 12 [0 – 29] and 94% previously received anti-TNFa therapy. Three-month and 6-month primary endpoints were achieved in 52% and 48%, respectively. Six-month remission was positively associated with Montreal B1 disease and negatively associated with perianal disease and baseline faecal calprotectin. Adverse events occurred in 11% of cases. Conclusion: These real-world data support the effectiveness and safety of vedolizumab in the treatment of IBD and give valuable insight into predictors of treatment outcomes. SUMMARY: This study reviews the safety and efficacy of treatment with vedolizumab for patients with inflammatory bowel disease across 9 Irish hospitals. It generates valuable and timely real-world data on treatment outcomes to add to the existing evidence base. Our population represents a refractory cohort with most patients previously exposed to at least one anti-TNFa agent and expressing an inflammatory phenotype. Results are reassuringly similar to larger international studies with additional insights into potential predictors of treatment response. This study further supports the safety and efficacy of vedolizumab in the treatment of inflammatory bowel disease. Key Summary: Vedolizumab has growing real world data on its safety and efficacy in the treatment of IBD. Data on predictors of response are lacking. Studies such as VARSITY require new real-world data to help identify the place VDZ will occupy in the treatment algorithm for IBD This study provides national Irish data on the safety and efficacy of VDZ in the treatment of IBD. It gives insight into various predictors of response for both UC and CD. It strengthens the available body of evidence on the use of VDZ and helps us determine its position on the treatment algorithm.